Molecular correlates of cisplatin-based chemotherapy response in muscle invasive bladder cancer by integrated multi-omics analysis - Ann Taber (Nature Portfolio, 2020)
There are currently only a few biomarkers to predict the response of muscle invasive bladder cancer to therapy. Here, the authors analyse 300 tumors using exome and RNA sequencing and find that tumors with a high degree of genomic instability and a non-basal/squamous gene expression subtype are most likely to respond to treatment.